(Des)proteção social e desastre tecnológico: um estudo sobre as medidas protetivas para as comunidades atingidas pelo desastre de Samarco/Vale/BHP Billiton - Mariano, João Marcos Mattos (2022)
Study on social protection for the people affected by the Samarco/Vale/BHP Billiton disaster in the Doce River, prepared as a dissertation presented to the Master's board in Social Policy of the Federal University of Espírito Santo. A critical bibliographic research was carried out, which scoured the studies in social policy and documents (minutes, deliberations and technical notes) produced by the Interfederative Committee (and the respective Technical Chambers of interest), as the plural government collegiate responsible for the supervision and guidance of compliance with the Terms of Transaction and Conduct Adjustment (TTAC) signed to promote the reparation of socio-environmental damage caused from the rupture of the tailing dam of Fundão, in Mariana/MG. The goal of this was to advance studies on social protection in the context of technological disasters, mainly with the objective of increasing the theoretical tooling available for the people affected by this type of destructive event. The main objective of the research was to try to analyze how social protection for the affected communities is normatively configured (in its scope) and how it is part of the landmarks of Brazilian capitalism. For this, the conformation of the Brazilian capitalist State was briefly analyzed, as the synergy between private capital and public determinations resulted in the molding of the capixaba part of the Doce river valley and, also, how these configurations contributed to the occurrence of the disaster. It was noticed that there is a link between the predatory exploitation of mineral resources (neoextractivism), the development model adopted in Brazil and the racist and technocratic modus operandi that marks the insertion of Brazilian social formation in the capitalist mode of production. The social protection structure created for the people affected and the neoliberal theoretical frameworks that serve as the foundation for the current Brazilian social policy were related. It was concluded for now that the marks of the national system of protection (focalization, privatization and decentralization), combined with the control of the process of supposed restoration by the polluting companies, exacerbated the general deficiencies of the model in the case analyzed.